The close-up and the reinvention of the subject: in search of the film character - Leal, João Vitor (2019)
This paper examines early cinema films in search of residues of the “invention” of the film character (and the corresponding “invention” of the film actor). We will analyze narrative and figurative strategies that trust the filmed body with its narrative load, making its appearances significant through the course of a story. We will highlight among these strategies the image of the actor’s face: from Transformation by hats (Lumière, 1895) to Fantômas (Feuillade, 1913), the close-up has become the most important device in allowing the viewer to anticipate and assign an individual identity to the human figure on screen, endowing it with psychological consistency and making it capable of fulfilling the narrative functions required by narrative films. We will see that, in addition to its essential contribution to the narrativization of the human face, the close-up also preserves its attractional force. This shows us that the “cinema of attractions” principle, easily noticeable in works by Méliès (The untamable whiskers, 1904) or A. E. Weed (Photographing a female crook and Subject for the rogue’s gallery, 1904), remains somewhat present in contemporary cinema – particularly in films that perform transformations and multiplications of characters’ bodies, thus complicating the relationship between body and identity. We believe that a better comprehension of early cinema close-ups is crucial for understanding the origins and complexities of the film character beyond the usual orbits of literature and theater.